Pengaruh Influencer Marketing dan E-WOM terhadap Keputusan Pembelian Produk Luxcrime pada Generasi Z di Kota Makassar Dimediasi Brand Image - Rahmawati Rahmawati; Romansyah Sahabuddin; Zainal Ruma; Wulansari Hasdiansa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of influencer marketing and electronic word of mouth (E-WOM) on purchasing decisions of Luxcrime products among Generation Z in Makassar City, both directly and indirectly through brand image as a mediating variable. This research employs a quantitative approach with an explanatory method. The population consists of Generation Z in Makassar City who actively use TikTok social media and are familiar with Luxcrime products. The sample comprised 150 respondents selected using a non-probability sampling technique with purposive sampling. Data were collected through online questionnaires distributed via Google Forms. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS version 4.0 software. The results indicate that influencer marketing and E-WOM have positive and significant effects on purchasing decisions and brand image. Furthermore, brand image has a positive and significant effect on purchasing decisions and positively and significantly mediates the influence of influencer marketing and E-WOM on purchasing decisions. This study provides implications for companies to strengthen brand image through effective influencer marketing strategies and credible E-WOM management on TikTok to enhance consumer purchasing decisions.